2017
DOI: 10.1167/iovs.16-20641
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Stat3 by a Small Molecule Inhibitor Slows Vision Loss in a Rat Model of Diabetic Retinopathy

Abstract: PurposeDiabetic retinopathy is a leading cause of vision loss. Previous studies have shown signaling pathways mediated by Stat3 (signal transducer and activator of transcription 3) play a primary role in diabetic retinopathy progression. This study tested CLT-005, a small molecule inhibitor of Stat3, for its dose-dependent therapeutic effects on vision loss in a rat model of diabetic retinopathy.MethodsBrown Norway rats were administered streptozotocin (STZ) to induce diabetes. CLT-005 was administered daily b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…Moreover, Xu et al demonstrated that STAT3 is up-regulated in DR-affected tissues and primary retinal vascular endothelial cells under high glucose (HG) conditions [39]. Increasing studies also showed that STAT3 could influence endothelial function in DR [40,41]. The results of our study also revealed that STAT3 expression was significantly increased in HG-treated ARPE-19 cells, which was obviously decreased after PG treatment.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, Xu et al demonstrated that STAT3 is up-regulated in DR-affected tissues and primary retinal vascular endothelial cells under high glucose (HG) conditions [39]. Increasing studies also showed that STAT3 could influence endothelial function in DR [40,41]. The results of our study also revealed that STAT3 expression was significantly increased in HG-treated ARPE-19 cells, which was obviously decreased after PG treatment.…”
Section: Discussionsupporting
confidence: 65%
“…We utilized STZ-diabetic rat models, which develop robust retinal neurodegeneration [20], to assess neuroprotective effects of PPARα activation in DR. We used optokinetic tracking to demonstrate that visual acuity, as detected by spatial frequency threshold [21], significantly decreased in diabetic rats and 8 and 12 weeks diabetic (p ≤ 0.001), and was partially restored by continuous oral treatment with PPARα agonist fenofibrate (p ≤ 0.05) (Fig 1A and 1B) . Fenofibrate did not affect visual acuity in non-diabetic rats.…”
Section: Resultsmentioning
confidence: 99%
“…We postulate that this seeming discrepancy could be because factors other than neurodegeneration contribute to optokinetic reflex in DR, and/or because mechanisms unrelated to PPARα affect long-term visual function. The optokinetic reflex declines in DR due to both neurodegeneration and unrelated pathologies such as increased cataract formation in DR and impaired reaction time in diabetic animals [21]. To our knowledge PPARα does not affect cataract formation or reaction time in diabetes, so the readout of neuroprotection in fenofibrate-treated diabetic animals may be precluded in part by these unrelated pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 factors influence endothelial function in DR [34,35]. Thus, we focused on the relationship between O-GlcNAcylation and STAT3 phosphorylation, and changes to specific STAT3 sites under different O-GlcNAcylation levels.…”
Section: Discussionmentioning
confidence: 99%